Techniques for Melon Grafting - Wenjing Guan; Xin Zhao (EDIS)
Grafting as a cultural practice for controlling soilborne diseases and improving abiotic stress tolerance has been widely used in vegetable production in many areas of Asia and Europe. Interest in vegetable grafting has been growing in the United States in recent years, as well. Cost, along with the desire to customize scion cultivars and the need to produce organic transplants, has led many small and organic growers to choose to graft plants by themselves. To help growers who are interested in grafting melon plants achieve a high graft survival rate, this 5-page fact sheet introduces commonly used grafting techniques and their application in specific circumstances. Written by Wenjing Guan and Xin Zhao, and published by the UF Department of Horticultural Sciences, December 2014.